AVALIAÇÃO NA EDUCAÇÃO INFANTIL: CONCEPÇÕES DE PROFESSORAS DE UMA PRÉ-ESCOLA DA CIDADE DE TOCANTINÓPOLIS - TO - Sodré, Zanadréya Marinho (Universidade Federal do Tocantins, 2022)
The act of evaluating in Early Childhood Education (EI) is a structural element of planning and pedagogical practice, but there are still difficulties and misunderstandings that can lead to different interpretations and execution on the part of EI teachers. In this sense, the present aims to reflect on the evaluation in EI from the understanding of preschool teachers. We opted for a qualitative approach with exploratory and bibliographic research, having the case study as a methodological strategy and the application of a questionnaire as an investigation technique. We had as a unit of analysis a preschool located in a peripheral neighborhood of the municipality of Tocantinópolis -TO and as the main bibliographic reference authors such as Hoffmann (2013), Fullgraff and Wiggers (2014). The data obtained indicate that there are mistakes in teaching practice, arising from the lack of specific continuing education on the subject.